Combining Bioinformatics Techniques to Study Diabetes Biomarkers and Related Molecular Mechanisms - Nie, Han; Zhang, Kaihua; Xu, Jiasheng; Liao, Kaili; Zhou, Weimin; Fu, Zhonghua (Frontiers in Genetics, 2020)
Objective: To explore the mechanism of plasma circulating miRNA-126 and miRNA-28-3p in diabetes mellitus (DM) patients，and to identify the related bioinformatics analysis． Methods: Randomly selected 120 DM patients as the observation group and 120 non- DM patients as the control group. The plasma circulating miRNA-126 and miRNA-28-3p were analyzed by qRT-PCR, and their target genes, biological information，related lncRNA and circRNA were predicted． Results: The circulating miRNA-126 (0.1162 ± 0.0236 vs 0.0018 ± 0.0862) and miRNA-28-3p (0.1378 ± 0.0268 vs 0.0006 ± 0.0167) levels in the observation group were significantly higher than those in the control group，and differences were statistically significant (P＜0.01). The Pearson correlation coefficient of miRNA-126 and miRNA- 28-3p was 0.4337 (P＜0.01). ROC curve analysis of miRNA-126 and miRNA-28-3p showed that the differences of the area under curve were statistically significant between the two groups (P＜0.01). Bioinformatics prediction showed that miRNA-126 and miRNA-28-3p may be involved in regulation of the insulin signaling pathway，insulin receptor signaling pathway，insulin / insulin growth factor signaling pathway, mitogen-activated protein kinase (MAPK) signaling pathway and angiogenesis. Moreover, it may be associated with a variety of lncRNA and cir-cRNA． Conclusion：Circulating miRNA-126 and miRNA-28-3p can be a potential biomarker of DM and it may play an important role in the DM by regulating insulin or insulin growth factor related signaling pathways．